PENGARUH NPM, ROI, EPS, DAN DPS TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN - Amruroh, M. Qoirul Jazik; Tohari, Amin; Zaman, Badrus (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This research is aimed at knowing the effect of the Net Profit Margin (NPM), Return On Investment (ROI), Earning Per Share (EPS), and Dividend Per Share (DPS) on the mining sector company stock price listed on the Indonesia Stock Exchange for the 2018-2020 period. Data analysis techniques using the regression panel with the fixed effect model 5% significance. The approach in this study used a quantitative causality method with a sample search using purposive sampling method. The result of this study is partial to NPM, ROI, and DPS have no significant effect on the mining company stock price, while EPS has a significant effect on the mining company stock price. Simultaneously NPM, ROI, EPS, and DPS have significant effect on the mining company stock price